Factors Influencing Breast Self-Examination (BSE) Behavior among Adolescent Girls: A Mixed Methods Approach to Early Breast Cancer Detection - Jaya, Herawati; Kumalasari, Intan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescence is a critical period of rapid physical and psychological development, making adolescents vulnerable to reproductive health issues. Breast cancer remains one of the leading health concerns for women in Indonesia, and early detection through breast self-examination (BSE) is crucial for reducing mortality rates. This study aimed to identify the barriers and needs of adolescent girls regarding early breast cancer detection through BSE using a mixed-methods approach. A mixed-methods design was used, combining a quantitative cross-sectional survey with qualitative in-depth interviews and Focus Group Discussions (FGDs). The target population was adolescent girls aged 15–24 years who attended high school and lived with parental support. The sample consisted of 172 adolescent girls, selected using purposive sampling for the quantitative analysis. Participants for the qualitative component were also chosen through purposive sampling. Quantitative data were collected using a questionnaire adopted from the 2017 Indonesian Demographic and Health Survey (IDHS) and analyzed through univariate and bivariate methods. Qualitative data were analyzed inductively using NVIVO software. BSE behavior was significantly influenced by age (p = 0.010), ethnicity (p = 0.000), social environment (p = 0.002), internet access (p = 0.011), information media (p = 0.000), family (p = 0.000), and peer influence (p = 0.000). Barriers included limited knowledge, lack of confidence, and communication gaps. Social and environmental factors significantly influence BSE behavior. Developing an interactive, application-based breast care education model can address these barriers and enhance BSE practices among adolescents.